1993
DOI: 10.1021/ef00042a061
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided molecular design study of coal model molecules. 3. Density simulation for model structures of bituminous Akabira coal

Abstract: The physical density of a macromolecular model (C390H362N6O38) for Japanese bituminous Akabira coal, which was previously constructed on the basis of the combined data of its Curie-point pyrolysis and CP/MAS 13C NMR, and of four kinds of the systematically modified models in the linkage fashion was estimated by the method using computer-aided molecular design (CAMD) software which we have previously proposed. The results suggest that (a) molecules consisting of a linear structure with branches are more suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…The energy minimization technique has been used as an additional tool for constructing coal structure to infer the most favorable spatial arrangement of groups concerned and determine whether the postulated model is consistent with the microporous nature of the coal. We and a few of other groups ,, have applied this technique on various proposed structural models. However, we have started to realize that previous works which applied this technique have failed to show various structural aspects for coals indicated above, such as the strained nature of the coal.…”
Section: Resultsmentioning
confidence: 99%
“…The energy minimization technique has been used as an additional tool for constructing coal structure to infer the most favorable spatial arrangement of groups concerned and determine whether the postulated model is consistent with the microporous nature of the coal. We and a few of other groups ,, have applied this technique on various proposed structural models. However, we have started to realize that previous works which applied this technique have failed to show various structural aspects for coals indicated above, such as the strained nature of the coal.…”
Section: Resultsmentioning
confidence: 99%
“…The densities determined for the coal structures to date are somewhat lower (4-20%) than experimental values. For one of the coals, several structural mod#i(;ations were made in the links between molecular clusters and the effects on density determined (23). In contrast to the studies referenced earlier, cross-linked structures were found to have a significant influence (reduction of ---10%) on density.…”
Section: Viastermentioning
confidence: 78%
“…Other researchers (Dong et al, 1993;Murta et al, 1993), have used a time step of 100 ps for molecules with a MW of 3000, i.e., similar to that of the endcut sample. The MD run time is dependent on the size of the target molecule.…”
Section: Computation Protocolmentioning
confidence: 99%